Enhancing energy efficiency through the incorporation of maqasid syariah knowledge : a review / Mohd Zin Kandar ... [et al.] - Kandar, Mohd Zin; Muszaffarsham, Nurul Hadirah; Mohd Husini, Elina; Md Norwawi, Norita; Khairi, Khairil Faizal (Universiti Teknologi MARA, Perak, 2023)
Energy efficiency (EE) is crucial in addressing environmental issues and organisational performance. Energy awareness and knowledge is needed in promoting EE practices. This paper aims to review Maqasid Syariah (MS) knowledge in enhancing good EE practices, and the objectives are to investigate the EE awareness, knowledge and practices in Malaysia, plus to explore the importance of MS knowledge. Qualitative method was employed through literature review and narrative study. A conceptual model of the incorporation of MS knowledge into EE awareness and knowledge is introduced. This conceptual model could be implemented to develop an enhanced good EE practices among occupants.